LEADERSHIP STYLES AND THEIR EFFECTIVENESS IN MANAGING REMOTE TEAMS: A PSYCHOLOGICAL ANALYSIS - Rania Khatib; Salma Hamdan; Rami Hariri (Research Psychologie, Orientation et Conseil, 2026)
The rise of remote work has introduced new challenges in leadership, requiring managers to adapt their styles to effectively manage geographically dispersed teams. Leadership styles play a crucial role in influencing team dynamics, motivation, and performance. As organizations continue to embrace remote work, understanding how different leadership styles affect the management of remote teams is essential for enhancing team effectiveness and productivity. This study aims to analyze the impact of different leadership styles transformational, transactional, and laissez-faire on the effectiveness of managing remote teams. The research seeks to identify which leadership styles are most effective in promoting employee engagement, motivation, and job satisfaction in a remote work environment. A mixed-methods approach was employed, utilizing both quantitative surveys and qualitative interviews. Data were collected from 250 employees working in remote teams across various industries. The surveys assessed leadership style preferences and the perceived effectiveness of leadership in managing remote teams, while the interviews provided deeper insights into the psychological impact of these leadership styles on team members. The findings revealed that transformational leadership had the most positive effect on team motivation, satisfaction, and performance, while laissez-faire leadership was associated with lower levels of engagement and job satisfaction. Transactional leadership had a moderate impact on team effectiveness.